Traffic-Adaptive Inter Wavelength Load Balancing for TWDM PON - Kamran Ali Memon; Qi Zhang; Rizwan Aslam Butt; Khalid Hussain Mohammadani; Muhammad Faheem; Noor ul Ain; Feng Tian; Xiangjun Xin (IEEE Photonics Journal)
This study presents a dynamic inter wavelength migration scheme for the optical network units (ONUs) employing linear regression machine learning method to equalize the traffic volume on all the wavelengths in time and wavelength division multiplexed passive optical network (TWDM PON). The proposed traffic-adaptive wavelength and bandwidth assignment (TA-WBA) scheme not only decreases upstream traffic delays but also offers 2.3% and 30% less delay on the wavelengths balancing the excessive load and 7% less upstream bandwidth waste, when evaluated against other load-balancing scheme.